2021
DOI: 10.1101/2021.01.22.427749
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emerging SARS-CoV-2 variants reduce neutralization sensitivity to convalescent sera and monoclonal antibodies

Abstract: SARS-CoV-2 Spike-specific antibodies contribute the majority of the neutralizing activity in most convalescent human sera. Two SARS-CoV-2 variants, N501Y.V1 (also known as B.1.1.7 lineage or VOC-202012/01) and N501Y.V2 (B.1.351 lineage), reported from the United Kingdom and South Africa, contain several mutations in the receptor binding domain of Spike and are of particular concern. To address the infectivity and neutralization escape phenotypes potentially caused by these mutations, we used SARS-CoV-2 pseudov… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 15 publications
4
33
0
Order By: Relevance
“…This is unsurprising given that there is no observed increase in reinfection reported with B.1.1.7 nor was there high seroprevalence in the UK during the emergence of this variant. Our finding is supported by many studies using B.1.1.7 viruses and PV which show either no reduction or a modest reduction in polyclonal serum titres (Collier et al, 2021;Diamond et al, 2021;Hu et al, 2021;Muik et al, 2021;Rees-Spear C et al, 2021;Wang et al, 2021;Wu et al, 2021). There is some evidence of heterogeneity of responses and neutralising titres for some individuals with initially low responses against WT virus can drop below limits of detection against the B.1.1.7 variant (Skelly et al, 2021).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This is unsurprising given that there is no observed increase in reinfection reported with B.1.1.7 nor was there high seroprevalence in the UK during the emergence of this variant. Our finding is supported by many studies using B.1.1.7 viruses and PV which show either no reduction or a modest reduction in polyclonal serum titres (Collier et al, 2021;Diamond et al, 2021;Hu et al, 2021;Muik et al, 2021;Rees-Spear C et al, 2021;Wang et al, 2021;Wu et al, 2021). There is some evidence of heterogeneity of responses and neutralising titres for some individuals with initially low responses against WT virus can drop below limits of detection against the B.1.1.7 variant (Skelly et al, 2021).…”
Section: Discussionsupporting
confidence: 83%
“…In some studies, PV bearing B.1.1.7 and wildtype S showed equivalent (<2-fold) neutralisation by convalescent sera (Collier et al, 2021;Rees-Spear C et al, 2021) or sera raised against vaccines (Muik et al, 2021;Wu et al, 2021). However, other studies found a modest decreased susceptibility (up to 4-fold) of B.1.1.7 PV to convalescent sera (Hu et al, 2021;Wang et al, 2021) or vaccine sera (Collier et al, 2021). Sera raised against BNT162b2 vaccine did not show decreased ability to neutralise a recombinant virus with 3 key B.1.1.7 S mutations; ∆69-70 + N501Y + D614G (Xie et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Of greatest concern has been the emergence of multiple strains of the B.1.351 lineage (also known as 501Y.V2), which were first reported in South Africa and have since spread globally (Tegally et al, 2021). This lineage bears three RBD mutations, K417N, E484K, and N501Y, in addition to several mutations outside of RBD, and several reports have suggested that convalescent and vaccinee sera have decreased cross-neutralization of B.1.351 lineage variants (Wang et al, 2021;Wibmer et al, 2021;Wu et al, 2021;Hu et al, 2021). A key limitation of several of these reports has been the use of single mutations or combinations of mutations that do not naturally occur.…”
Section: Introductionmentioning
confidence: 99%
“…23 Early studies assessing the neutralising ability of sera from convalescent patients and vaccinees against pseudoviruses expressing some mutations present in B.1.1.7 or the entire B.1.1.7 spike protein suggest no or little reduction in neutralisation compared with older circulating viral variants. [24][25][26][27][28] Early reports suggest that vaccine efficacy might not be reduced against this variant. 4…”
Section: Implications Of All the Available Evidencementioning
confidence: 99%